2022
DOI: 10.1007/s00344-022-10648-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Jasmonic and Salicylic Acid on Enzymatic Changes in the Root of Two Alyssum inflatum Náyr. Populations Exposed to Nickel Toxicity

Abstract: Salicylic acid (SA) and jasmonic acid (JA) as plant growth regulators (PGRs) have the potential to ameliorate plant development and tolerance to deleterious effects of toxic metals like nickel (Ni). Therefore, the current study was carried out to evaluate SA and JA's interactive effect on the root antioxidative response of two Alyssum in atum Nyár. populations against Ni-toxicity. Two A. in atum species under Ni-stress conditions (0, 100, 200, and 400 µM) were exposed to alone or combined levels of SA (0, 50, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Antioxidant enzymes have been mainly reported to be the first line of defensive and protective mechanisms against any environmental factor such as abiotic stresses ( Lei et al., 2022 ; Mittler et al., 2022 ; Najafi-Kakavand et al., 2022 ; Rahman et al., 2022 ; Raza et al., 2022a ; Raza et al., 2022b ; Shahid et al., 2022 ; Shaukat et al., 2022 ; Bhardwaj et al., 2023 ). At first, the superoxide radicals are converted to H 2 O 2 by SOD activity which can be further decomposed into H 2 O by CAT and peroxidases ( Hasanuzzaman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant enzymes have been mainly reported to be the first line of defensive and protective mechanisms against any environmental factor such as abiotic stresses ( Lei et al., 2022 ; Mittler et al., 2022 ; Najafi-Kakavand et al., 2022 ; Rahman et al., 2022 ; Raza et al., 2022a ; Raza et al., 2022b ; Shahid et al., 2022 ; Shaukat et al., 2022 ; Bhardwaj et al., 2023 ). At first, the superoxide radicals are converted to H 2 O 2 by SOD activity which can be further decomposed into H 2 O by CAT and peroxidases ( Hasanuzzaman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds of Alyssum inflatum Nyár. of the M population were collected from serpentine sites in Marivan (35 ° 13.625′ N; 46 ° 27.184′ E), and the seeds of NM populations were gathered from non-serpentine of Shahu sites (34 ° 56′ 47′′ N; 46 ° 27′ 41′′ E), respectively from West of Iran in summer of 2015 10 by Naser Karimi (Department of Biology, Razi University, Kermanshah, Iran) according to the institutional, national and international guidelines and laws. The permission to collect plants (license code: IR.KUMS.REC.1401.512) was obtained from the Pharmaceutical Sciences Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran, which identifies the institutional licensing committee that approves the collection of plants and experiments, including any relevant details.…”
Section: Methodsmentioning
confidence: 99%
“…has been identified as a Ni-hyperaccumulating plant native to the Ni-rich serpentine regions of Western Iran. 10 , 11 . For the first time, Ghaderian et al (2007) reported that A. inflatum can accumulate more than 3,700 (μg Ni g −1 shoot DW) 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of Alyssum in atum Nyár. of the M population were collected from serpentine sites in Marivan (35•13.625′N; 46•27.184′E), and the seeds of NM populations were gathered from non-serpentine of Shahu district (34 56′47″N; 46 27′41″E), respectively from west of Iran in summer of 2015 12 by Naser Karimi (Department of Biology, Razi University, Kermanshah, Iran) according to the institutional, national and international guidelines and laws. The permission to collect plants (license code: IR.KUMS.REC.1401.512) was obtained from the Pharmaceutical Sciences Research Center, Kermanshah University of Medical Sciences, Kermanshah, Iran, which identi es the institutional licensing committee that approves the collection of plants and experiments, including any relevant details.…”
Section: Plant Preparation and Treatmentsmentioning
confidence: 99%
“…has been introduced as a Ni-hyperaccumulating plant native to the Ni-rich serpentine regions of western Iran. 12,13 . For the rst time, Ghaderian et al (2007) reported that A. in atum can accumulate more than 3,700 mg Ni in its aerial part dry weight (DW) 14 .…”
Section: Introductionmentioning
confidence: 99%